Illustration anglophobe dans La France illustrée (1898) - La France illustrée | 1898 (Wikimedia Commons, 1898)
Notice iconographique issue de Wikimedia Commons. Titre: Illustration anglophobe dans La France illustrée (1898). "The English in Siam, Egypt, the Sudan and other places". The Anglophobic caption has been added to a painting by Léontine Malbet, who occasionally included rats and white mice in her paintings. Published in the 19 November 1898 issue of the French weekly La France illustrée during the Fashoda Incident.
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; Patrimoine; Wikimedia Commons; tableau; Iconographie